Constitutionalism and the politics of accommodation in multinational democracies - Lluch, Jaime; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This collection argues that although constitutionalism has traditionally been the primary mechanism for facilitating the mutual accommodation of sub-state and state national societies in plurinational states.
Keywords: Political science; Culture -- Study and teaching; Cultural policy; Organization; Planning; Comparative politics; International relations; Political Science and International Relations; Comparative Politics; International Relations; Cultural Policy; Cultural and Media Studies, general; Political Science; Organization